Electrical characterization of the polyaniline including boron/p-type silicon structure for optical sensor applications - Yakuphanoglu, Fahrettin; Şenkal, B. Filiz (Elsevier BV, 2008)
Abstract The charge transport properties of polyaniline including boron (PANI-B)/p-type silicon diode have been investigated. The current–voltage characteristics of the device have been investigated under white and ultraviolet light illuminations. Electronic parameters such as the barrier height, diode ideality factor and series resistance, were determined from the current–voltage (I–V) characteristics in the dark of the device and were found to be 0.81 eV, 3.58 and 1.67 × 106 Ω, respectively. The photocurrent for the device was found to be 0.857 μA. The open circuit voltage (Voc = 119.6 mV) under UV illumination is higher than that of the open circuit voltage under (Voc = 57.6 mV) white light illumination, although the intensity of the UV light has lower value. The obtained photovoltaic results suggest that the polyaniline including boron/p-type silicon device can be used as a sensor in optical applications.